SILIH ASAH, SILIH ASIH, AND SILIH ASUH VALUES IN DEVELOPING ELEMENTARY SCHOOL STUDENTS’ SOCIAL ETHICS: A SYSTEMATIC LITERATURE REVIEW: English - sri handarini; Yusuf Tri Herlambang (SOSIOEDUKASI, 2026)
This systematic literature review examines the implementation of Sundanese philosophical values "Silih Asah, Silih Asih, Silih Asuh" in developing social ethics in elementary schools. The study analyzes 40 relevant articles from Sinta 2 and Scopus-indexed journals published between 2022-2025. Using the PRISMA framework, this review identifies key themes, implementation strategies, and outcomes of integrating local wisdom into elementary education. Results show that these values significantly enhance students' social competence, empathy, and collaborative skills. The findings suggest that incorporating indigenous philosophical values into school curricula can effectively bridge cultural preservation with modern educational goals.